2018
DOI: 10.3390/atmos9020054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Common Assumptions Regarding Aerosol Composition and Mixing State on Predicted CCN Concentration

Abstract: Abstract:A 4-year record of aerosol size and hygroscopic growth factor distributions measured at the Department of Energy's Southern Great Plains (SGP) site in Oklahoma, U.S. were used to estimate supersaturation (S)-dependent cloud condensation nuclei concentrations (N CCN ). Baseline or reference N CCN (S) spectra were estimated using κ-Köhler Theory without any averaging of the measured distributions by creating matrices of size-and hygroscopicity-dependent number concentration (N) and then integrating for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…For M BC e , c CO , and the particle concentrations in the accumulation mode range (N acc ), in the Aitken mode range (N Ait ), and in the total particle population (N CN,10 ), 4-6 years of ATTO site measurements were available. Additionally, M BC e data measured at the ZF2 site, located 40 km northwest of Manaus, were used to reflect the conditions back to 2008 (e.g., Martin et al, 2010a). In terms of sources and conditions, the ATTO and ZF2 sites are comparable (Saturno et al, 2017a;.…”
Section: Seasonal Cycles Of Remote-sensing and In Situ Datamentioning
confidence: 99%
“…For M BC e , c CO , and the particle concentrations in the accumulation mode range (N acc ), in the Aitken mode range (N Ait ), and in the total particle population (N CN,10 ), 4-6 years of ATTO site measurements were available. Additionally, M BC e data measured at the ZF2 site, located 40 km northwest of Manaus, were used to reflect the conditions back to 2008 (e.g., Martin et al, 2010a). In terms of sources and conditions, the ATTO and ZF2 sites are comparable (Saturno et al, 2017a;.…”
Section: Seasonal Cycles Of Remote-sensing and In Situ Datamentioning
confidence: 99%
“…Number concentrations fluctuate in response to the nitrate and organic aerosol cycle on short time scales and synoptic weather variability on longer time scales. During winter months, the inorganic aerosol composition at the site is dominated by nitrate aerosols (Jefferson et al, 2017;Mahish et al, 2018) and hygroscopicity derived from scattering measurements is largest during those months (Jefferson et al, 2017).…”
Section: Growth Factormentioning
confidence: 99%
“…Depending on location and local emissions, heterogeneity in hygroscopicity frequently decreases in the early afternoon, when photochemistry increases the available concentrations of condensible species (e.g., [48,53]). Mahish et al (2018) [54] compared predicted CCN concentrations based on different simplifications of the mixing-state using long-term observations from the Southern Great Plains site in Oklahoma, USA. They found that a size-resolved internally-mixed representation of the aerosol mixing state performed modestly better (normalized mean bias (NMB) 1 to 2%, coefficients of determination (R 2 ) about 0.85) compared to either a fully internally-mixed, size-resolved externally-mixed, or a fully externally-mixed representation of the mixing state (NMB 10 to 21%, −9%, and 0 to 7%, respectively; R 2 about 0.8).…”
Section: Impacts On Ccn Concentrationsmentioning
confidence: 99%
“…These errors depend on model spatial resolution, and on the representations of the aerosol size distribution, aerosol processes, and aerosol optical properties, in addition to the true mixing state of the aerosol population. With these caveats in mind, a size-resolved internally-mixed representation has been shown to frequently overestimate CCN concentrations by 10% to 20% [54,[56][57][58]61], and absorption coefficients of BC by 20% to 40% [49,[56][57][58]. In the case of CCN concentrations and BC absorption, these overestimates will be greater near source regions, while overestimates in wet deposition will lead to greater errors in hydrophobic aerosol concentrations far from source regions (e.g., [64]).…”
Section: Summary and Recommendationsmentioning
confidence: 99%